Footprints : sharing experiences between travellers. - Lim, Nicholas Shuqing. (2011)
Overseas travel is a popular activity which has a large social aspect. It is organic and interpersonal; a place leaves a mark on us and we leave our own mark on a place and its people. These influence experiences and stories which we proceed to share with friends and other travellers. Through studies, it has been demonstrated that these experiences can be beneficial to improving harmony and the appreciation of other cultures. This project aims to find a way for young travellers to connect with one another through three-dimensional forms which maximise personal expression, facilitate the sharing of travel experiences and create a focal point over which people can bond. Research was conducted on the nature of interpersonal interactions between travellers and their motivations. The intended outcome is an enriched and vibrant travel experience that can be shared with other people present and otherwise. Of the possibilities studied, the solution that allow users to directly alter its appearance and add their personality to it in infinite ways was chosen. The three-dimensional form reflects the organic and social nature of travel among young people and is self-sufficient to allow its users to participate with just their hands and their minds.